Placement of Covered Self-Expandable Metal Biliary Stent for the Treatment of Severe Postsphincterotomy Bleeding: Outcomes of Two Cases - Marta Di Pisa; Ilaria Tarantino; Luca Barresi; Davide Cintorino; Mario Traina (Gastroenterology Research and Practice)
We report two cases of severe postsphincterotomy bleeding in an adult and a pediatric patient treated, as first options, with available techniques to induce hemostasis without success. Because of persisting bleeding, an expandable, partially covered, metallic stent was placed into the choledocho to mechanically compress the bleeding site. The bleeding was stopped. In the following days, both patients remained hemodynamically stable with no further episodes of bleeding. We believe that the application of a covered metallic stent in a severe postendoscopic-sphincterotomy bleeding, refractory to injection therapy, should be considered to avoid additional interventions, which carry a higher risk of complications, even in pediatric patients.